1988
DOI: 10.1021/bi00425a002
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 reverse transcriptase: crystallization and analysis of domain structure by limited proteolysis

Abstract: Bacterially expressed recombinant HIV-1 reverse transcriptase is active as both a homodimer of Mr 66,000 subunits and a heterodimer of Mr 66,000 and 51,000 subunits. The heterodimer is formed by cleavage of a C-terminal fragment from one Mr 66,000 polypeptide, which occurs during purification and crystallization of reverse transcriptase. Thus, crystals obtained from purified Mr 66,000 polypeptide preparations consisted of an apparently equimolar mixture of Mr 66,000 and 51,000 polypeptides, which were apparent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
95
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(108 citation statements)
references
References 32 publications
(52 reference statements)
11
95
1
Order By: Relevance
“…There is a region of the 66-kDa protein that is susceptible to the viral protease and to unrelated proteases. We have not seen as much specificity in the cleavage of the 66-kDa HIV-1 RT when we incubated the protein with nonviral proteases at 23" as Lowe et al (1988) observed when they performed digestions at 0". They reported additional cleavages when the incubation temperature was raised from 0 to 21" and the incubation time was increased.…”
Section: Proteolytic Digestion Of Hiv-1 Rtmentioning
confidence: 67%
See 3 more Smart Citations
“…There is a region of the 66-kDa protein that is susceptible to the viral protease and to unrelated proteases. We have not seen as much specificity in the cleavage of the 66-kDa HIV-1 RT when we incubated the protein with nonviral proteases at 23" as Lowe et al (1988) observed when they performed digestions at 0". They reported additional cleavages when the incubation temperature was raised from 0 to 21" and the incubation time was increased.…”
Section: Proteolytic Digestion Of Hiv-1 Rtmentioning
confidence: 67%
“…These results suggest that cleavage occurs either at or very near the same site in the in vitro digestion and in virions. The 66-kDa form can be cleaved to a 5 1 -kDa form by a protease present in E. co/i (Lowe et al, 1988). Although the HIV-l protease made in E. co/i was purified by HPLC, we considered the possibility that a contaminating bacterial protease could have been responsible for cleaving the HIV-1 RT in vitro.…”
Section: Proteolytic Digestion Of Hiv-1 Rtmentioning
confidence: 99%
See 2 more Smart Citations
“…The HIV-1 PR generates F440 as the carboxy end of the p51 subunit (Mizrahi et al, 1989;Bathurst etal., 1990;Graves etal., 1990). Bacterially expressed HIV-1 RT, on the other hand, has a heterogeneous C-terminus centered around P433 (Lowe et al, 1988). The crystal structure of the HIV-1 PR with and without substrate analogs (Miller et al, 1989) shows that it is highly unlikely that the protease could reach the cleavage site unless the RNase H domain of HIV-1 RT p66 is partially or totally unfolded upon dimerization (Jacobo-Molina and Arnold, 1991).…”
Section: Expression Of Hiv-1 Reverse Transcriptasementioning
confidence: 99%